Economic and Social Impacts of Public Housing Development in Bali Province: Input-Output Analysis - Christine Diandini; Gede Sri Darma (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid population growth in Denpasar, Bali, has increased housing demand, particularly for civil servants facing limited affordable options. This study aims to analyze the economic and social benefits and impacts of the State-Owned Apartments developed by the Ministry of Finance in Bali Province. Data were collected through document studies, secondary data from the Central Bureau of Statistics, and in-depth interviews with residents, asset managers, and local community leaders. The Input-Output analysis reveals that every rupiah invested generates an economic output of 1.45 rupiah, with significant impacts on construction, electricity and gas supply, and accommodation sectors. Civil servants reported reduced living costs, increased savings, and improved workplace access. Socially, the apartments enhance quality of life, provide a secure and child-friendly environment, and strengthen community bonds. The project optimizes state asset management and improves civil servants’ well-being, but its focus on civil servants limits broader community benefits. These findings suggest that State-Owned Apartments are a viable model for urban housing, though future initiatives should include diverse populations. Studies with updated data are needed to capture long-term impacts.